UPAYA HUKUM TERHADAP DEBITUR WANPRESTASI DALAM PERJANJIAN KREDIT DENGAN JAMINAN HAK TANGGUNGAN DI BANK BRI CABANG SANGGAU - NIM. A1012181051, HENRY DIO SANTANA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The activity of borrowing and lending money through credit agreements with collateral in the form of security rights is a common practice in banking. However, in practice, defaults by debtors often occur, hindering the repayment of creditors' funds. This thesis analyzes the legal measures taken by creditors, particularly Bank BRI Sanggau Branch, in dealing with defaulting debtors in credit agreements with security rights as collateral. Therefore, the research addresses the issue of